Il sogno della farfalla - Fagioli, Massimo (Il sogno della farfalla, 2009)
The story of a boy who chooses to speak only when he recites plays is the subject matter of Massimo Fagioli’s screenplay, published for the first time in the first issue (1, 1992) of this journal which bears its title, and subsequently made into a film by the director M. Bellocchio (1994).